Deployment of Autonomous Vehicles to Support Emergency Response During Crisis - Owais, Omar; Ghaffarianhoseini, Ali; Alqudah, hamzah; Poshdar, Mani (Information Systems for Crisis Response and Management (ISCRAM), 2022)
Emergency response services face massive pressure during global crises, such as COVID-19. The food supply logistics sector is one of the pressures that impacted the emergency response services, due to crisis restrictions. A regulatory framework to deploy autonomous vehicles, in any nominated country, has been presented to boost the food supply logistics as an emergency response to critical situations to serve isolated areas. This framework resulted in three steps to deploy AVs in the nominated country, which are evaluating their legislation, modifying their existing regulations accordingly, and ensuring the full deployment of the innovative technology. This is done by minimising person-to-person contact during the transportation and distribution phase. In conclusion, fully autonomous vehicles can help lift the pressure from the emergency response teams in the food supply transportation and distribution phase to meet the basic living requirements for human needs during global crises.